2013
DOI: 10.4018/ijcbpl.2013100101
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Paper, Learning from Screens

Abstract: Electronic screens on laptop and tablet computers are being used for reading text, often while multitasking. Two experimental studies with college students explored the effect of medium and opportunities to multitask on reading (Study 1) and report writing (Study 2). In Study 1, participants (N = 120) read an easy and difficult passage on paper, a laptop, or tablet, while either multitasking or not multitasking. Neither multitasking nor medium impacted reading comprehension, but those who multitasked took long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 49 publications
1
9
0
5
Order By: Relevance
“…Seven experimental studies investigated study time (see Table 3), and three correlation studies investigated the ability to focus on an academic activity (see Table 2). First, four of the seven experimental studies on study time found that youth who used media while studying needed more time to complete an academic task, r range = .26 to .44 (Bowman et al, 2010;Fox et al, 2009;Pool et al, 2003a;Subrahmanyam et al, 2013). The other three studies found no relationship (Cool et al, 1994;Pool et al, 2000Pool et al, , 2003b.…”
Section: Findings On Study-related Attitudes and Behaviorsmentioning
confidence: 93%
See 3 more Smart Citations
“…Seven experimental studies investigated study time (see Table 3), and three correlation studies investigated the ability to focus on an academic activity (see Table 2). First, four of the seven experimental studies on study time found that youth who used media while studying needed more time to complete an academic task, r range = .26 to .44 (Bowman et al, 2010;Fox et al, 2009;Pool et al, 2003a;Subrahmanyam et al, 2013). The other three studies found no relationship (Cool et al, 1994;Pool et al, 2000Pool et al, , 2003b.…”
Section: Findings On Study-related Attitudes and Behaviorsmentioning
confidence: 93%
“…In addition, six of ten studies found that media use while reading interfered with reading comprehension, r range = À.24 to À.51 (Armstrong & Greenberg, 1990;Furnham, Gunter, & Peterson, 1994;Jeong & Hwang, 2012;Pool et al, 2000Pool et al, , 2003aPool et al, , 2003b. The other four studies found no effect (Bowman, Levine, Waite, & Gendron, 2010;Cool, Yarbrough, Patton, Runde, & Keith, 1994;Lee, Lin, & Robertson, 2012;Subrahmanyam et al, 2013). In addition to examining reading outcomes, two experimental studies examined how math performance is affected by television use while working on a math assignment (see Table 3).…”
Section: Homework Outcomesmentioning
confidence: 94%
See 2 more Smart Citations
“…Dos de cada tres estudiantes españoles de educación secundaria postobligatoria publican en las redes sociales las experiencias de sus actividades de ocio más importantes, lo que refuerza las conclusiones emanadas de estudios previos (Almansa et al, 2013;Espinar y González, 2009;Llamas y Pagador, 2014;Subrahmanyam et al, 2015) que constatan que las redes sociales se constituyen en un medio de comunicación de gran importancia entre los jóvenes actuales, ya que significan un punto de encuentro fundamental para este colectivo.…”
Section: Discusión Y Conclusionesunclassified